Thermo-mechanical assessment of high entropy (Fe-Ni-Cx (X=0.3-0.5), (Fe-Cr-Cx (X=0.3-0.5) ternary alloys system using calphad method : DOI: 10.48129/kjs.18613 - shah, Waseem Ullah; khan, Dil faraz khan; yin, haiqing yin; jan, saeed ullah jan (Kuwait Journal of Science, 2023)
The thermodynamical assessment of high entropy alloys (Fe-Ni-Cx (X=0.3-0.5)), (Fe-Cr-Cx (X=0.3-0.5)) system is performed in this research work through Fe-demo database and Thermo-Calc software package. The high energy thermal analysis is manipulated for yield strength from FCC to BCC, precipitation from cementite to M7C3 (grain boundaries), Crack Susceptibility Coefficient for Fe-Ni-C ,Fe-Cr-C ternary alloys system at (1900-3000)K temperature with constant atmospheric pressure of 106 Pascal. The highest crack susceptibility coefficient for Fe-Cr-C, Fe-Ni-C system is found 2.70, 2.60 with mass percent of C 0.11%, at 3000K of temperature with Mass percent. Yield strength from FCC to BCC is found 798 MPa, 36 MPa for Fe-Cr-C, Fe-Ni-C ternary alloys at the cost of 2.2, 0.1 mass% C. Phase transition is noted from cementite to M7C3 at 1346.77339 K. FCC_A1#3 phases with 0.98772 moles and 0.01228 mole Of M7C3 with 0 moles of M23C6 carbide phases observed. The comprehensive line investigation of mechanical properties is justified with simulation/computational inputs. The results are feasible for industrial sectors and metallurgical centers for operation. The alloy shows equilibrium and good stability. ERRATUM In the Kuwait Journal of Science, Vol.50, Issue No.(3A), July 2023, pp. 1-12 of the article titled, “Thermo-mechanical assessment of high entropy (Fe-Ni-Cx (X=0.3-0.5), (Fe-Cr-Cx (X=0.3-0.5) ternary alloys system using calphad method,” by Waseem Ullah Shah, Dil Faraz Khan, Haiqing Yin, and Saeed Ullah there has been an error in the alloying composition of Table 2 and Table 3. In alloying three elements, either Fe,Cr,C / Fe,Ni,C, the total composition should not exceed 100 mass%. Accordingly, the composition of the Mass% Fe column in both Table 2 and Table 3 have been revised to provide the corrected alloying elements results in consideration of this fact.